2017
DOI: 10.1038/am.2017.204
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient voltage control of spin and enhanced interfacial perpendicular magnetic anisotropy in iridium-doped Fe/MgO magnetic tunnel junctions

Abstract: Voltage control of spin enables both a zero standby power and ultralow active power consumption in spintronic devices, such as magnetoresistive random-access memory devices. A practical approach to achieve voltage control is the electrical modulation of the spin-orbit interaction at the interface between 3d-transition-ferromagnetic-metal and dielectric layers in a magnetic tunnel junction (MTJ). However, we need to initiate a new guideline for materials design to improve both the voltage-controlled magnetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 42 publications
4
76
0
Order By: Relevance
“…Voltage-torque (VT) switching is another attractive method for low power writing, which is based on voltage control of magnetic anisotropy (VCMA) in a thin ferromagnetic film [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The mechanism of the VCMA in a MgO-based MTJ is considered as the combination of the selective electron/hole doping into the d-electron orbitals and the induction of a magnetic dipole moment, which affect the electron spin through the spin-orbit interaction [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-torque (VT) switching is another attractive method for low power writing, which is based on voltage control of magnetic anisotropy (VCMA) in a thin ferromagnetic film [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The mechanism of the VCMA in a MgO-based MTJ is considered as the combination of the selective electron/hole doping into the d-electron orbitals and the induction of a magnetic dipole moment, which affect the electron spin through the spin-orbit interaction [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…in a thin film can be substantially modified by the external factors such as the film thickness and the strain with the substrate [30,42]. Similarly, the strength of the DMI (D) can be controlled through the choice of the spin-orbit coupled material as it is associated with the interaction at the interface [39].…”
Section: Resultsmentioning
confidence: 99%
“…outside the currently considered range (for instance, those adopted for PdFe/Ir(111) [45]). A recent experiment suggests that the anisotropy modulation in the range of 300-400 kJ/m 3 can be within reach via VCMA [30]. The magnetoelastic effect is expected to be effective as well [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Noguchi et al reported VC-MRAM circuits for ultralarge last level cache memory, in which the voltage to switch the magnetization is as high as 2.2 V [10], which is larger than the standard CMOS power-supply voltage of less than 1.2 V. The necessity of such a large voltage originates from limited amounts of anisotropy modulation coefficients by E-field. To overcome this issue, the material development of the free-layer material is now underway [88][89][90][91][92]. Another issue to be addressed is the small time window for the writing.…”
Section: Progress Of Vc-mrammentioning
confidence: 99%